MOTIVASI PETANI DALAM BUDIDAYA TANAMAN CABAI DI DESA KIRITANA KABUPATEN SUMBA TIMUR - Aji, Yana Kariri; Katongu Retang, Elfis Umbu (Fakultas Pertanian, Universitas Janabadra, 2024)
This research measures the level of motivation and analyzes the influence of farmers' internal and external factors on their motivation in cultivating chili plants in Kiritana. The sample was determined using the saturated sampling or census method, and the number of samples used in this research was 50 respondents. Analysis of the level of farmer motivation was carried out using a Likert scale, then to determine the influence of internal and external factors on farmer motivation, analysis was carried out using multiple linear regression model equation analysis. The results of the analysis illustrate that the motivation of farmers in cultivating chili plants in Kiritana Village is in the high category. The results of the influence analysis explain that partially the factors age, income, government policy, and market opportunities have a significant influence on farmer motivation, while the factors education, land area, experience, number of family dependents, and technology do not have a significant influence. Taken together, the factors age, education, income, number of family dependents, experience, land area, government policy, market opportunities and technology have a significant influence on farmers' motivation in cultivaating chili plants in Kiritana Village.